THE EFFECTS OF TEACHING THE BIOLOGICAL SCIENCES CURRICULUM STUDY ELEMENTARY SCHOOL SCIENCES PROGRAM ON ATTITUDES TOWARD SCIENCE AMONG ELEMENTARY SCHOOL TEACHERS. - Tolman, Richard R.; Barufaldi, James P. (Journal of Research in Science Teaching, 1979)
The article cites a study about the outcomes of teaching the biological sciences curriculum study elementary school sciences program (ESSP) on elementary school teachers' attitudes toward science. The new ESSP group has no idea in terms of placement into experimental or control groups prior to pre-testing and post-testing. It was observed that the combined new and experienced ESSP educators were more optimistic compared with the control group. The differences between the pretest and posttest scores for the new ESSP teachers are beyond the boundaries of the standard error of measurement. Teachers with insufficient science background tend to be more positive in their attitudes toward science.